2019
DOI: 10.1111/zph.12646
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic relationships between Leishmania infantum from dogs, humans and wildlife in south‐east Spain

Abstract: Leishmania infantum causes human and canine leishmaniosis. The parasite, transmitted by phlebotomine sand flies, infects species other than dogs and people, including wildlife, although their role as reservoirs of infection remains unknown for most species. Molecular typing of parasites to investigate genetic variability and evolutionary proximity can help understand transmission cycles and designing control strategies. We investigated Leishmania DNA variability in kinetoplast (kDNA) and internal transcribed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 50 publications
8
53
0
Order By: Relevance
“…Vectors, susceptible hosts and L. infantum (pathogen) need to converge in time and space for efficient pathogen transmission (Kent, ). PCR detection of L. infantum in three wolves and one brown bear indicates that infection is present in the park, and canids are competent L. infantum reservoirs (Ortuño et al, ; Risueño et al, ). In addition, our results support the role of canines as common hosts of sand flies in the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vectors, susceptible hosts and L. infantum (pathogen) need to converge in time and space for efficient pathogen transmission (Kent, ). PCR detection of L. infantum in three wolves and one brown bear indicates that infection is present in the park, and canids are competent L. infantum reservoirs (Ortuño et al, ; Risueño et al, ). In addition, our results support the role of canines as common hosts of sand flies in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, L. infantum DNA was diagnosed by PCR in skin samples from three wolves ( Canis lupus ) and one brown bear ( Ursus arctos ) from the Murcia city wildlife park, in south‐east Spain (Ortuño et al, ; Risueño et al, ). The area is L. infantum endemic, and the estimated PCR prevalence was 67% in dogs (Chitimia et al, ), 32% in free wildlife (mostly foxes, rabbits and rodents) (Risueño et al, ) and 8% in human blood donors (Pérez‐Cutillas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These results show the genetic complexity of Leishmania spp. populations which circulate in a different geographical area but in the same species (Cupolillo et al, 1998;Ortuño et al, 2019). On the other hand, isolated samples from Brazilian domestic cats were phylogenetically close to isolated samples from domestic dogs, which indicates that possibly L. infantum circulating in Brazil is present in both species.…”
Section: Discussionmentioning
confidence: 76%
“…Natural infection by L. infantum in wildlife species in South-Eastern Spain was described in captive wolves and brown bears, and in free-ranging wildlife species such as foxes, rabbits and rodents [ 17 , 18 ]. In addition, Muñoz et al [ 2 ] reported sand fly vector abundance in the ‘Terra Natura’ wildlife park.…”
Section: Discussionmentioning
confidence: 99%